Recurrent Cardiac Myxoma with Unusual Histopathology - Rao, Rajesh Kishan (International Journal of Innovative Research in Medical Science, 2017)
Recurrence of cardiac myxoma is rare, seen in about 2-3% of patients, in sporadic cases, although recurrence is frequently seen in familial type. The Authors report a case of non-familial right atrial myxoma, after successful resection of left atrial myxoma with no recurrence in left atrium. The case is unusual both for its location in the right atrium and histopathology.